Cities and natural process : a basis for sustainability - Hough, Michael (Routledge, 2004)
"'Cities and Natural Process' is a discussion of the fundamental conflict in the perception of nature and an expression of the essential need for an environmental view when approaching urban design. Michael Hough outlines how natural and human processes are altered by the city and how this leads to changes in attitudes and cultural values. He reveals how alternative values based on ecological insights offer the possibility of a constructive relationship with the urban environment. Practical examples of opportunities that are often unrecognized serve to illustrate the potential for beneficial change. While retaining the existing structure of the first edition, each of the chapters has been revised to take into account recent theoretical and practical developments. A completely new concluding chapter has been added that draws together the themes of the volume and links these to broader landscape issues such as greenway systems, landscape ecology, and green infrastructure."--Publisher's website